ALGORITHM AS A BORDER: DIGITAL SOVEREIGNTY AND THE NEW GEOPOLITICS OF INFORMATION (REMUNOM, 2026)
This article analyzes the phenomenon of algorithmic nationalism as a contemporary expression of the geopolitics of information and the coloniality of power mediated by recommendation systems, digital platforms, and algorithmic governance. It argues that algorithms no longer function as neutral technical tools but have become strategic infrastructures capable of organizing the circulation of content, shaping collective attention, and influencing democratic dynamics. The study brings together theoretical contributions on algorithmic political bias, communication research on psychosocial engineering, microtargeting, and disinformation, and the analysis of the TikTok case between the United States and China as an empirical landmark of the algorithmic fragmentation of the internet. It argues that the requirement for national versions of algorithms signals the emergence of a new form of sovereignty, in which control over AI models becomes a matter of national security and democratic stability. The article also contends that this process deepens global asymmetries, as countries in the Global South remain large-scale data providers and users of opaque systems without effective control over their governance. It concludes that algorithmic nationalism reconfigures the struggle for informational power, shifting the center of international relations toward the control of systems that structure the digital public sphere.